The carnivorous carnival - Snicket, Lemony; Helquist, Brett (London : Egmont, 2003)
On the run as suspected murderers, the unlucky Baudelaire orphans find themselves trapped in the Caligari Carnival, where they must masquerade as freaks in order to hide from the evil Count Olaf.
Keywords: Fiction; Humorous fiction; Orphans -- Fiction